PENGEMBANGAN KAPASITAS ORGANISASI DALAM PENANGANAN KASUS KEKERASAN DALAM RUMAH TANGGA (KDRT) TERHADAP ANAK : (STUDI PADA UNIT PELAKSANA TEKNIS DINAS PERLINDUNGAN PEREMPUAN DAN ANAK (UPTD PPA) KOTA TANGERANG SELATAN) - Nuraulia, Ridela; Gandini Purbaningrum, Dini (Cahaya Ilmu Bangsa, 2025)
Abstract Domestic Violence (DV) is an important issue, due to the increasing cases of domestic violence in the world, including in Indonesia, and the negative effects it has on women and children. To create an area that is safe from violence, the South Tangerang City Government has provided various protection facilities for women and children, one of which is the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA). Organizational capacity development at the UPTD PPA of South Tangerang City refers to the process of developing organizational capacity in carrying out functions, solving problems and achieving organizational goals. The purpose of this study is to describe the development of organizational capacity at the UPTD PPA of South Tangerang City and whether organizational development can increase the effectiveness and efficiency of services for handling domestic violence (DV) cases against children. The method used is descriptive qualitative with the theory of Organizational Capacity Development according to Leavitt (1983) in (Irviana & Salomo, 2021), namely physical resource capacity, operational process capacity, and human resource capacity. The results of the study found that the development of organizational capacity at the UPTD PPA of South Tangerang City still needs improvement because in terms of physical resource capacity, the organizational structure of the UPTD PPA is not in accordance with applicable regulations and there is no Safe House for victims of domestic violence. The operational process capacity shows that the work procedures are good and orderly, but socialization regarding the complaint flow to the community is still needed to avoid misunderstandings. For human resource capacity, although the behavior of staff in serving the community is good, staff still experience obstacles due to the workload and the increasing number of cases of violence. Therefore, the development of human resource capacity, both in quality and quantity, is very much needed to increase the effectiveness of case handling. Keywords: Capacity Development, The Protection of Women and Children Organization, Domestic Violence. Abstrak Kekerasan Dalam Rumah Tangga (KDRT) menjadi isu penting, dilatarbelakangi dengan meningkatnya kasus KDRT di Dunia termasuk di Indonesia. Untuk mewujudkan wilayah yang aman dari kekerasan, Pemerintah Kota Tangerang Selatan telah menyediakan berbagai fasilitas perlindungan perempuan dan anak, salah satunya Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak (UPTD PPA). Pengembangan kapasitas organisasi di UPTD PPA Kota Tangerang Selatan mengacu kepada proses pengembangan kapasitas organisasi dalam menjalankan fungsi, menyelesaikan masalah dan mencapai tujuan organisasi. Tujuan penelitian ini yaitu memaparkan pengembangan kapasitas organisasi di UPTD PPA Kota Tangerang Selatan dan apakah pengembangan organisasi dapat meningkatkan efektivitas dan efisiensi pelayanan penanganan kasus kekerasan dalam rumah tangga (KDRT) terhadap anak. Metode yang digunakan yaitu kualitatif deskriptif dengan teori Pengembangan Kapasitas Organisasi menurut Leavitt (1983) dalam (Irviana & Salomo, 2021) yaitu kapasitas sumber daya fisik, kapasitas proses operasional, dan kapasitas sumber daya manusia. Hasil penelitian menemukan bahwa pengembangan kapasitas organisasi di UPTD PPA Kota Tangerang Selatan masih membutuhkan peningkatan karena dari segi kapasitas sumber daya fisik, struktur organisasi UPTD PPA belum sesuai dengan peraturan yang berlaku dan belum ada Rumah Aman untuk korban KDRT. Kapasitas proses operasional menunjukkan bahwa prosedur kerja sudah baik dan teratur, namun sosialisasi mengenai alur pengaduan kepada masyarakat masih diperlukan untuk menghindari kesalahpahaman. Untuk kapasitas sumber daya manusia, meskipun perilaku staf dalam melayani masyarakat baik, staf masih mengalami kendala karena beban kerja dan jumlah kasus kekerasan yang terus meningkat. Kata kunci: Pengembangan Kapasitas, Organisasi PPA, KDRT.